Rancangan Sistem Rekomendasi Terapis Berbasis Form Rating di Mariaty’s Spa - Mega Ayunda Putri; Agus Gunawan; Yoke Pribadi; Angela Caroline; Shelvi Shelvi (Business Administration Department - Universitas Katolik Parahyangan, 2017)
The growth rate of spa industry in Bandung is getting higher each year which can be proven by the level of development recorded in BPS 2015 approximately 7.63%. It is make Mariaty's Spa need to think of new ways to mantain their sales. Therefore, the aim of this research is to proposed system of therapist recommendations based on the therapist's highest rating for maintaining sales.This research used an exploratory method. All data were obtained from interview with receptionist Mariaty's Spa and analyzed using the MIT 90's Framework that describes the state of internal and external Mariaty's Spa. Moreover, the author’s using BPMN to analyze the actual business process and describe the design of the proposed new business processes.